Physiological and Biochemical Effects of Potassium Deficiency on Apple Tree Growth - Evangelia-Vasiliki Ladikou; Gerasimos Daras; Marco Landi; Theocharis Chatzistathis; Thomas Sotiropoulos; Stamatis Rigas; Ioannis E. Papadakis (Horticulturae)
Potassium (K) is an essential mineral element that supports numerous plant processes, including photosynthesis, enzyme activation, osmoregulation, and nutrient balance. This study investigated how K deficiency impacts growth, physiological performance, and carbohydrate metabolism in ‘Granny Smith’ apple trees grafted onto M9 rootstock. The experimental material was cultivated hydroponically in a greenhouse under four K regimes, including 0.00, 0.75, 1.50, and 3.00 mM K, over 159 days. Deficiency symptoms such as chlorosis and necrosis were observed primarily in basal leaves. A reduced net photosynthetic rate in top and basal leaves was linked to a decreased stomatal conductance, thus limiting CO2 uptake (stomatal limitations of photosynthesis). Photosynthetic pigments, including chlorophyll a, chlorophyll b, and carotenoids, were also significantly reduced in K-limited leaves. Furthermore, photochemical performance of PSII also declined under K deficiency, with lower electron transport rates, PSII efficiency, and photochemical quenching (non-stomatal limitations of photosynthesis). While the photosynthetic rate declined under K deficiency conditions, the carbohydrate metabolism remained relatively stable without significant variation in total, translocating, or non-translocating sugars. Notably, an increase in sucrose-to-hexose ratio under low K suggests changes in sugar partitioning and utilization. Biomass allocation was also affected, with a notable decrease in the shoot-to-root ratio, mainly due to increased dry weight of roots, likely reflecting an adaptive response to enhance K uptake. Our study provides valuable insights into sustainable K fertilization practices aiming to maximize photosynthetic capacity, pigment content, and biomass production. These findings emphasize the importance of considering rootstock/scion interactions in future research to enhance apple tree vigor and productivity.